2017
DOI: 10.1002/fam.2489
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐coordinated epoxy polymers with suppressed combustibility. Preparation technology, thermal degradation, and combustibility test of new epoxy‐amine polymers containing the curing agent with chelated copper(II) carbonate

Abstract: Summary The diethylenetriamine chelate complex of copper(II) carbonate—DETA‐CuCO3 (a fire retardant hardener of epoxy resins)—and the CuCO3‐containing epoxy‐amine polymers—DGEBA/DETA‐CuCO3(6), DGEBA/DETA‐CuCO3(12), DGEBA/DETA‐CuCO3(40), and DGEBA/DETA‐CuCO3(80) with suppressed combustibility—have been obtained in the DETA‐DGEBA‐CuCO3 system (DETA and DGEBA are diethylenetriamine and bisphenol A diglycidyl ether, respectively). The DETA‐CuCO3 chelate complex was characterized by X‐ray powder diffraction, infrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…Thermal analysis is one of the important methods to study organic compounds. It allows investigating not only the thermal stability of substances, but also the nature of the processes that occur when they are heated [9,10].…”
Section: Resultsmentioning
confidence: 99%
“…Thermal analysis is one of the important methods to study organic compounds. It allows investigating not only the thermal stability of substances, but also the nature of the processes that occur when they are heated [9,10].…”
Section: Resultsmentioning
confidence: 99%
“…Combustibility parameters were determined for samples of DGEBA/pepa ‐CuSiF 6 (I), DGEBA/pepa ‐CuSiF 6 (II), DGEBA/pepa ‐CuSiF 6 (III), and DGEBA/pepa ‐CuSiF 6 (IV), as well as DGEBA/pepa (for comparison) according to all‐Union State Standard 12.1.044‐89 (Supporting Information), which is described in detail in, 15 using the “Ceramic tube” (CT) apparatus. The results of the CT measurements are presented in Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…Said studies were started relatively recently and those are currently developing rapidly. Already the first tests carried out in this area revealed a high fire‐retardant ability of substances of this type 12‐16 . In particular, it was found that epoxy resins cured by amine complexes of d ‐metals have higher ignition and self‐ignition temperatures, spread flame more slowly and are characterized by lower values of the maximum temperature of gaseous products of combustion and smoke formation in comparison with the known epoxides cured by traditional amine hardeners.…”
Section: Introductionmentioning
confidence: 99%
“…The combustibility parameters for the DGEBA/PEPA, DGEBA/PEPA-CuSO4, (DGEBA/PEPA)2-(CuOH)2CO3 and DGEBA/PEPA-CuSiF6 composites were determined according to all-Union State Standard 12.1.044-89 using the ceramic tube (CT) method, which is described in detail in (Lavrenyuk et al, 2018b). Its gist consists of temperature conditions that promote polymer material combustion.…”
Section: Determination Techniques Of the Fire-hazardous Indicesmentioning
confidence: 99%
“…) Unlike organic salts, inorganic salts are non-combustible. That is why our work developing epoxy-amine composites Lavrenyuk et al, 2016а;Lavrenyuk et al, 2018a;Lavrenyuk et al, 2018b) has used chelate complexes composed of exclusively inorganic salts from copper(II) and polyethylenepolyamine (PEPA).…”
Section: Introductionmentioning
confidence: 99%